Enhanced vortex pinning in Nb using proximity effect through organic molecules. (1st February 2018) - Katzir, Eran; Sukenik, Nir; Alpern, Hen; Yochelis, Shira; Millo, Oded; Paltiel, Yossi
Abstract: While the superconductor proximity effect is well understood in layered superconductor/normal-metal junctions, its understanding is quite limited in systems involving nanoparticles (NPs) and molecules. In recent studies, a unique inverse proximity effect phenomenon was found in which the critical temperatures of Nb films surprisingly increased upon the chemical attachment of gold NPs. Concomitantly, the tunneling density of states on and around the gold NPs was significantly modified, showing either zero-bias peaks or the development of proximity gaps in the NPs. These results seem to be related to the molecule-mediated coupling strength. Here, we study the strong molecular coupling regime of such an architecture, for which proximity gaps are induced in Au NPs. We show that significant pinning is induced in a periodic array of Au NPs coupled to a superconducting surface via organic molecules. The pinning potential in this case is stronger than the potential achieved through the direct proximity of Au or Ni islands to the superconducting surface. A matching field magnetoresistance signal can only be identified using the hybrid Au/organic-linker/Nb system. In this case, the matching vortex lattice density is higher than the saturation number. These results suggest that the NP-Nb electrical coupling through the molecules induces a resonance behavior, which modifies the local pairing amplitude.